Granqvist, ethnograpy and political commitment - Samuli Lähteenaho (Babylon)
This article is a series of short reflections on anthropology in the Middle East, building on a comparison between two careers in Finnish ethnography in the Levant at two different times. The first is that of Hilma Granqvist’s arrival to pursue anthropology in Palestine in the 1920s during the colonial era of the British mandate. The second is that of my own arrival in the 2010s as an early career anthropologist to Lebanon, and also in some ways to Palestine.